Hermeneutika Al-Qur’an dalam Perspektif Farid Essack - Munfarida, Elya (Fakultas Syariah IAIN Purwokerto, 2008)
Reception hermeneutic toward Al-Qur’an in Farid Essack perspective is not only able to accommodate the history of texts but also to give space for readers to ‘have dialogues’ with text based on social contexts. This approach is applied as a to get objective interpretation especially in South Africa with its characteristic (rasism, economic exploitation, etc ).